Talaqqi-Based Instruction and Qur’anic Memorization Fluency: a Correlational Study Within Contemporary Tahfidz Education - Hamiyah Zuleika Alifah; Ilham Madani Pasaribu (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2026)
Qur’anic memorization emphasizes not only the ability to retain verses but also fluency in reciting them accurately and continuously according to tajwid rules. The talaqqi method, which involves direct teacher–student interaction, is widely used in Qur’anic learning; however, its relationship with memorization fluency requires empirical verification. This study aims to examine the correlation between the implementation of the talaqqi method and students’ Qur’anic memorization fluency at Ma’had Abu Ubaidah bin Al-Jarrah Medan. This research employed a quantitative approach with a correlational design. Data were collected using standardized scales measuring the implementation of the talaqqi method and the level of memorization fluency, and were analyzed using Pearson Product Moment correlation. The results indicate that the implementation of the talaqqi method is categorized as good, with a mean score of 104.6, while students’ memorization fluency is also at a good level, with a mean score of 68.37. The correlation analysis reveals a positive and statistically significant relationship between the talaqqi method and memorization fluency (r = 0.318; p = 0.005). Furthermore, the coefficient of determination (r² = 0.101) shows that the talaqqi method contributes 10.1% to students’ memorization fluency, while the remaining variance is influenced by other factors. These findings confirm that talaqqi is an important instructional component in improving Qur’anic memorization fluency.